c.1 - Khurshida Begum (Calcutta, 1988)
This is a study of the on going dispute between India and Bangladesh which arose because of the Farakka Barrage Project of India to divert Ganga flow. It is found that the tension over the Farakka Barrage as it is today is rooted in some spheres of deep concern of the food crisis population pressure, qualitative balance of the environment etc, and in the growing awareness of the various economic uses of water, the precious life-going natural resources of our planet. The diversion of a large quantum of the downstream Ganga flow through the Farakka Barrage has its effect on the ecosystem of the region. An attempt has been made in this research to analyse how the situation has taken a complicated turn because of the underlying economic political and strategic factors. Nevertheless it comes forth from this study that in the ecosystem nation states are inextricably linked with one another beyond their political boundary lines or seperate administrative devices.
Keywords: Farakka Barrage